2007
DOI: 10.1177/145749690709600112
|View full text |Cite
|
Sign up to set email alerts
|

A 19-Year Review of Paediatric Patients with Acute Scrotum

Abstract: The high probability of SCT among those admitted to an emergency department within six hours from the onset of the symptoms justifies immediate surgical exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
2
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 13 publications
4
66
2
5
Order By: Relevance
“…In our study, four patients had torsion of the testicular appendage and all of them were 4 years old. In the study carried out by Mäkelä et al [13] on 388 scrotal examinations, there were 100 patients (26%) with SCT, 174 patients (45%) with torsion of the testicular appendage, 38 patients (10%) with epididymitis, 32 patients (8%) with incarcerated inguinal hernia, and 44 patients (11%) with other conditions. In a 25-year review of acute scrotum in South Africa during the period 1970-1996, 199 boys were studied.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, four patients had torsion of the testicular appendage and all of them were 4 years old. In the study carried out by Mäkelä et al [13] on 388 scrotal examinations, there were 100 patients (26%) with SCT, 174 patients (45%) with torsion of the testicular appendage, 38 patients (10%) with epididymitis, 32 patients (8%) with incarcerated inguinal hernia, and 44 patients (11%) with other conditions. In a 25-year review of acute scrotum in South Africa during the period 1970-1996, 199 boys were studied.…”
Section: Discussionmentioning
confidence: 98%
“…Differential diagnosis of acute scrotum by history and physical examination is difficult in one-third of patients, mandating a rapid and accurate diagnostic tool (Pakzad, 2001). The historilogy and clinical examination can significantly straitened the discriminating diagnosis of an acute scrotum, if not found the correct cause (Mäkelä, Lahdes-Vasama, Rajakorpi, & Wikström, 2007;Yang et al, 2011). The precise diagnosis is of great importance since curative consequences varied regard to the reason of the state (Asgari et al, 2006;Molokwu, Somani, & Goodman, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In our hospital, ultrasound with an expert sonologist, is only available during day time and not during the late afternoon and at night. As pain and swelling of scrotum are the most common symptoms in testicular torsion and also there are paucity of diagnostic tools, so some studies suggest early surgical exploration [15][16][17] , as we have done this for the indicated patients in our study.…”
Section: Discussionmentioning
confidence: 99%